Some Stream Water Quality Characteristics of Two Small Logged Over Watersheds in Selangor - Lai, Food See; Awang Jalil, Norajiki (1988)
A study of selected stream water quality parameters was carried out in two forested watersheds with varying degrees of disturbance. The study period of six months from August 1983 to January 1984 involved regular sampling at between 1400 and 1500 hours. Results indicate all parameters observed from the relatively more disturbed watershed WA were higher than the less disturbed basin WB. Mean values of stream water quality parameters of WA and WB respectively are as follows: water temperature - 25.3 and 25.PC; dissolved oxygen - 6.7 and 6.4 ppm; pH - 5.55 and 5.25; conductivity 16.0 and 11.3 J.Unhos/cm; suspended solids - 22 and 7 mg/l and; total dissolved solids - 36 and 31 mg/l. The findings suggest logging operations had varying influences on the water quality parameters. Although affected, the water quality remains good, aided by environmental considerations during logging operations.